2009
DOI: 10.3844/ajabssp.2009.97.104
|View full text |Cite
|
Sign up to set email alerts
|

Soil Erosion Prediction Based on Land Use Changes (A Case in Neka Watershed)

Abstract: Problem statement: Land use change has transformed a vast part of the natural landscapes of the developing world for the last 50 years. Land is a fundamental factor of production and though much of the course of human history, it has been tightly coupled with economic growth. Soil erosion by water is one of the most important land degradation processes in the Mediterranean basins. The unplanned land use change within and near a fast growing agricultural land in Neka River Basin, led to an accelerated erosion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…It has been repeatedly emphasized in literature that factors causing landscape heterogeneity are either natural or anthropogenic in nature or a combination of both (Alfred et al, 2010;Solaimani et al, 2009;Elhadi et al, 2009;Marian et al, 2009). Natural factors can be site factors such as soil, elevation, slope or disturbances as typhoons and landslides.…”
Section: Discussionmentioning
confidence: 99%
“…It has been repeatedly emphasized in literature that factors causing landscape heterogeneity are either natural or anthropogenic in nature or a combination of both (Alfred et al, 2010;Solaimani et al, 2009;Elhadi et al, 2009;Marian et al, 2009). Natural factors can be site factors such as soil, elevation, slope or disturbances as typhoons and landslides.…”
Section: Discussionmentioning
confidence: 99%
“…Yasouri et al (2012) reported on a two-fold increase in sedimentation yield after the rangeland reduction by 13%. After a particular land use/cover alteration (cropland to forest), Solaimani et al (2009) found a sedimentation yield decrease of 89.24%. According to Wayne et al (2002), cultivated basins produced by almost 50% more sediments than the forest/woodland basins.…”
Section: Discussionmentioning
confidence: 99%
“…Expansion of urban areas is the main causes of land use change (Solaimani et al, 2009). In urban development, construction sector plays major role.…”
Section: Introductionmentioning
confidence: 99%